Amelioration of ischaemia reperfusion-induced cerebral injury in mice by liposomes containing Allium cepa fraction administered intranasally. (12th November 2018) - Singh, Varinder; Krishan, Pawan; Shri, Richa
Abstract: Neuroprotection in ischaemic stroke prevents neuronal injury and subsequent death. Our earlier work revealed the neuroprotective effect of ethylacetate fraction (EF) obtained from Allium cepa outer scales in a mouse model of cerebral ischaemia–reperfusion (I–R) injury. The present study was designed to develop and optimize a liposomal delivery system for EF, along with its biological assessment. Thin film hydration method was used for the preparation of liposomal formulation. The prepared liposomes were optimized with respect to particle size, size distribution and encapsulation efficiency (EE) and characterised on the basis of zeta potential, in vitro release, morphology (TEM) and physical stability. The biological activity of the optimized liposomal formulation (EF-L; 8.5 mg/kg, intra-nasal) was evaluated after induction of cerebral injury in the experimental animals. Neuroprotective effects were assessed in terms of improvement of cognitive/sensorimotor functions and reduction of cerebral infarct size and brain oxidative stress. EF-L (particle size of 204.93 ± 7.96 nm; EE of 88.02 ± 2.09%; zeta potential of –20.8 ± 1.24 mV) showed controlled release pattern; spherical shape and were physically stable for 60 days at 4 °C. Intra-nasal administration of EF-L produced significant neuroprotection in mice at 1/10th the oral dose. Thus, EF-L may be developed as a neuroprotective formulation.